PENGARUH KEBIASAAN KONSUMSI MINUMAN KEMASAN BERPEMANIS TERHADAP BERAT BADAN SISWA KELAS X SMK BINA SEHAT - Putri damayanti; Irwandi Rahmat; Rezki (Jurnal Suara Kesehatan, 2023)
Currently, various types of drinks have been packaged in instant form to make it easier for consumers to enjoy various flavors of drinks. Packaged sweetened drinks are a type of drink that is dense in calories and high in sugar but low in nutrition. This research aims to see the influence of the habit of consuming packaged drinks in class X students of Bina Sehat Vocational School. This research is qualitative in nature with data collection using a questionnaire distributed to students. The results showed that the habit of consuming packaged beverages in class X students of Bina Sehat Vocational School was included in the rare category with an average body weight of 45.5 kg which was included in normal nutritional status.